CUSTOM JOURNALING BOOK UNTUK MENINGKATKAN KESEHATAN MENTAL PADA GENERASI Z - Angelica Fayola Ayu Paramita; Paulina Tjandrawibawa (Universitas Ciputra Surabaya, 2021)
This research takes theme of improving mental health in writing which aims to increase public awareness of the importance of literacy culture, especially writing which is start to reduce in Indonesia. Because of rapid technological development, people start abandon the literacy culture. Writing has many benefits for human mental health. The research method that used is literature studies through journals and books for the source of discussion. The results of the research are proved that gadgets have a negative effect for human health. In addition, the chance of z generation has mental health disorders are very high and writing can help to reduce that mental health disorder. That writing have many benetifs than typing. Keywords: Writing, Mental Health, Z Generation , Gadget